OTHERING PROCESSES AMONG BRAZILIAN INTERACTANTS ON THE INTERNET - Signorini, Inês (Revista da Anpoll, 2016)
The article focuses on the process of othering as it is embodied in linguistic interactions among Brazilians on the Internet during the last decade, when socioeconomic mobility expanded the access and the adherence to practices involving digital technological resources by different social Brazilian groups. By othering, it means any linguistic-discursive action by which an individual or group is classified as “not one of us” (difference and strangeness). Considering that the construction of the Other is made up of social action; has an ideological component; and that an exercise of power is always present, the aim herewith is to show that othering processes in focused interactions instantiate overlaps, interceptions and tangencies between different space-temporal scales which constitute the contemporary Brazilian “reality”. Observational data from a research project carried out since 2005 about internet-mediated interactions among Brazilians will be used to illustrate the contentions put forth in this paper. This work is licensed under a Creative Commons Attribution 3.0 License.